MASLAHAH SEBAGAI UPAYA MEMBANGUN EKONOMI BERDASARKAN ETIKA - Nuraini, Arif; Muttaqin, Muhammad Ngizzul (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
As an activity that has never escaped human life, economic practice is a necessity and a necessity. In reality economic practice is adomed by various phenomena that oppress certain groups. Economic practices that void personal desires seem to override the human side. The practice of trade monopolies, usury practices, and fraud seem to have become ingrained in today?s economic practices. As a religion that has a goal maslahah, thisphenomenon certainly must be responded to by the Islamic religion through the principles of Islamic economics. As a literature-based study and literature study, this paper seeks to provide ethical principles in economic practice through the realization of error. The findings in this paper are expected to provide guidelines in economic practice.